Sang Gambar Otoritas Ilahi: Pelayanan yang Bertanggung Jawab dengan Lensa Vocation Dei dan Imitatio Christi - Tarigan, Karel Benridho (Sekolah Tinggi Teologi Sumatera Utara, 2024)
Church ministers organize church life institutionally and guide church member's spirituality. This research focuses on the spiritual dimension, especially on morality. Church Ministers are seen as role models and are not treated as examples only, but also as actors of good-moral. The benchmark of good-moral in this research is Christ as the main nomos because the church minister is the image of divine authority in the church's life. however, how can Christ the Nomos be interpreted, so that the service carried out is full of passion and responsibility? Therefore, this research uses the idea of vocation Dei which has nuances of responsibility fulfillment. In addition, the idea of imitatio Christi and the theology of participation are elaborated to emphasize that fulfilling the responsibility of the call to serve is an attempt to demonstrate the image of divine authority. The results of this study show that as an image of divine authority, ecclesiastical ministers are responsible for